2009
DOI: 10.1189/jlb.0609400
|View full text |Cite
|
Sign up to set email alerts
|

Basophils preferentially express mouse mast cell protease 11 among the mast cell tryptase family in contrast to mast cells

Abstract: Tryptases and chymases are the major proteins stored and secreted by mast cells, and they have various biological functions. However, the nature of proteases produced by basophils has been poorly characterized, particularly in mice. mMCP-11 is the most recently discovered mast cell tryptase in mice and was originally identified as Prss34, which is transcribed in some mast cell-like cell lines and at the early stage in the culture of BMMC with IL-3. Curiously, Prss34 is preferentially expressed in the BM and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 56 publications
4
114
1
Order By: Relevance
“…Our prior study showed that the number of infiltrative basophils in skin lesions of IgE-CAI was higher than that of dermal mast cells (19.4 cells/mm 2 versus 8.2 cells/mm 2 ). 31 Thus, basophils may be equally or even more important than mast cells as sources of PGD2 production in IgE-CAI. PGD2 is one of the important mediators responsible for the development of IgE-CAI as evidenced by unpublished observation (Y. Matsushima) that the administration of an antagonist against the PGD2 receptor CRTH2 ameliorated skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prior study showed that the number of infiltrative basophils in skin lesions of IgE-CAI was higher than that of dermal mast cells (19.4 cells/mm 2 versus 8.2 cells/mm 2 ). 31 Thus, basophils may be equally or even more important than mast cells as sources of PGD2 production in IgE-CAI. PGD2 is one of the important mediators responsible for the development of IgE-CAI as evidenced by unpublished observation (Y. Matsushima) that the administration of an antagonist against the PGD2 receptor CRTH2 ameliorated skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bone marrow cells expressing mMCP-8, a specific marker for basophils, 31 were positive for both H-PGDS and mPGES1 by immunohistochemical analysis ( Figure 6B). These results show that basophils express H-PGDS as well as PGES, thereby producing both PGD2 and PGE2.…”
Section: Basophils Express H-pgds and Pgesmentioning
confidence: 99%
See 1 more Smart Citation
“…2, B and C). In addition, to confirm that the highly enriched cells were indeed basophils, cytospins were stained with mMCP-8, which has been reported as a specific marker for basophils, and Wright-Giemsa staining, respectively (31,36). Immunofluorescence analysis indicated that the population was ϳ100% positive for mMCP-8 (Fig.…”
Section: The Number Of Basophils In Mln and Ox40l Expression On Thesementioning
confidence: 99%
“…To characterize the sorted BM-Bas, cytospins were made. A part of them were stained with Wright-Giemsa and the others were fixed with 4% (v/v) paraformaldehyde, then permeated with 0.1% (v/v) Triton 100 and blocked with 10% (w/v) bovine serum albumin, stained with purified antimMCP-8 antibody (Ab) (clone TUG8, Biolegend) and FITCconjugated rabbit polyclonal secondary Ab to rat, and counterstained with DAPI (4,6-diamidino-2-phenylindole) (30,31).…”
Section: Mice-ox40mentioning
confidence: 99%